2004
DOI: 10.1111/j.1365-2362.2004.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

FH clinical phenotype in Greek patients with LDL‐R defective vs. negative mutations

Abstract: The homogenous molecular basis of familial hypercholesterolaemia in Greece facilitates the application of a DNA diagnostic strategy based on the origin of the patient. The early mutation analysis would add valuable information on the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…Mutation prevalence in the proband group was 34.2% compared to 50.9% in the group of relatives consistent with earlier reports [3,18]. However, as the prevalence in probands depends on the inclusion criteria and the test used different prevalences have been reported for probands.…”
Section: Discussionsupporting
confidence: 85%
“…Mutation prevalence in the proband group was 34.2% compared to 50.9% in the group of relatives consistent with earlier reports [3,18]. However, as the prevalence in probands depends on the inclusion criteria and the test used different prevalences have been reported for probands.…”
Section: Discussionsupporting
confidence: 85%
“…In that study, it was hypothesized that the differential binding to ANP of small and medium HDLs could be the result of the exposure of a larger number of hydrophobic domains in small HDLs due to the partial delipidation that occurs during the remodeling process. Unforeseen were the lower levels of LDL-C, which could be attributed to the type of LDLR mutation, since as we have previously shown the type of LDLR defect affects the LDL-C levels (23). Additionally, other lipid-lowering genes have been reported to affect LDL-C levels in FH patients (24).…”
Section: Discussionmentioning
confidence: 93%
“…In Greece, 16 mutations in the LDLR are responsible for heterozygous FH and among them V408M, G528D, C6W and S265R account for 73% of heterozygous FH probands [2,3]. The impact of these mutations on the LDL-R function has been characterised by considerable variability and in this regard we have previously shown that the carriers of receptor negative mutations have higher levels of total cholesterol (TC), LDL cholesterol and higher prevalence of TX compared to carriers of receptor defective mutations [3]. However, the great variability in lipid levels and the prevalence of CAD may not be solely explained by the type of LDLR mutation.…”
Section: Introductionmentioning
confidence: 99%